Neonatal thrombocytopenia associated with placental insufficiency: A case report - Handini, Laksmi Suci (Journal of Diverse Medical Research: Medicosphere, 2024)
Thrombocytopenia commonly found in neonatal, especially in ill-appearing infant. However, it may happened in well-appearing infant. This following case showed infant could have thrombocytopenia right after delivery process. This thrombocytopenia phenomenon assumed due to plasental insufficiency in mother with preeclampsia. Placental insufficiency is a condition where the placenta, which is responsible for providing nutrients and oxygen to the developing fetus, is not functioning adequately. Finding the correct etiology made early interventions given in this patients.